Identification of a major QTL for flag leaf glaucousness using a high-density SNP marker genetic map in hexaploid wheat - Chun-lian LI; Ting-ting LI; Tian-xiang LIU; Zhong-pei SUN; Gui-hua BAI; Feng JIN; Yong WANG; Zhong-hua WANG (Journal of Integrative Agriculture, 2017)
Cuticular wax plays an important role in protecting land plant against biotic and abiotic stresses. Cuticular wax production on plant surface is often visualized by a characteristic glaucous appearance. This study identified quantitative trait loci (QTLs) for wheat (Triticum aestivum L.) flag leaf glaucousness (FLG) using a high-density genetic linkage map developed from a recombinant inbred line (RIL) population derived from the cross Heyne×Lakin by single-seed descent. The map consisted of 2 068 single nucleotide polymorphism (SNP) markers and 157 simple sequence repeat (SSR) markers on all 21 wheat chromosomes and covered a genetic distance of 2 381.19 cM, with an average marker interval of 1.07 cM. Two additive QTLs for FLG were identified on chromosomes 3AL and 2DS with the increasing FLG allele contributed from Lakin. The major QTL on 3AL, QFlg.hwwgr-3AL, explained 17.5–37.8% of the phenotypic variation in different environments. QFlg.hwwgr-3AL was located in a 4.4-cM interval on chromosome 3AL that was flanked by two markers IWA1831 and IWA8374. Another QTL for FLG on 2DS, designated as QFlg.hwwgr-2DS which was identified only in Yangling in 2014 (YL14), was flanked by IWA1939 and Xgwm261 and accounted for 11.3% of the phenotypic variation for FLG. QFlg.hwwgr-3AL and QFlg.hwwgr-2DS showed Additive×Environment (AE) interactions, explaining 3.5 and 4.4% of the phenotypic variance, respectively. Our results indicated that different genes/QTLs may contribute different scores of FLG in a cultivar and that the environment may play a role in FLG.